2023
DOI: 10.3390/plants12091815
|View full text |Cite
|
Sign up to set email alerts
|

Negative Impacts of Arsenic on Plants and Mitigation Strategies

Abstract: Arsenic (As) is a metalloid prevalent mainly in soil and water. The presence of As above permissible levels becomes toxic and detrimental to living organisms, therefore, making it a significant global concern. Humans can absorb As through drinking polluted water and consuming As-contaminated food material grown in soil having As problems. Since human beings are mobile organisms, they can use clean uncontaminated water and food found through various channels or switch from an As-contaminated area to a clean are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 379 publications
0
6
0
Order By: Relevance
“…Similarly, the application of Bacillus faecalis ( B. faecalis ) positively impacted various parameters under arsenic stress in our maize crop study. B. faecalis mitigated the adverse effects of arsenic on plant growth parameters, including plant height, leaf length, leaf width, shoot length, root length, and biomass [ 85 , 86 ]. This effectiveness may be due to B. faecalis role as a rhizobacterium, influencing nutrient availability, promoting root development, and regulating plant metal uptake, as supported by previous studies [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the application of Bacillus faecalis ( B. faecalis ) positively impacted various parameters under arsenic stress in our maize crop study. B. faecalis mitigated the adverse effects of arsenic on plant growth parameters, including plant height, leaf length, leaf width, shoot length, root length, and biomass [ 85 , 86 ]. This effectiveness may be due to B. faecalis role as a rhizobacterium, influencing nutrient availability, promoting root development, and regulating plant metal uptake, as supported by previous studies [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, research has demonstrated that As III is more toxic to plants than As V , primarily due to its elevated solubility in water [ 43 ]. Overall, As causes major damage to the morpho-physiological aspects of several plant species [ 44 ]. At the morpho-physiological and metabolic stages, As leads to a decline in germination, leaf wilting, and biomass and disrupts the water balance.…”
Section: Impacts Of Nps On Plants Under Hm Toxicitymentioning
confidence: 99%
“…At the biochemical levels, the overproduction of ROS induced by As is highly detrimental to plants. This is because ROS can severely disrupt plant metabolisms and lead to oxidative damage in important bio-macromolecules like carbohydrates, proteins, nucleic acids, and lipids [ 44 , 247 , 248 ]. Nanotechnology has emerged as a significant asset for advancing plant defenses against environmental challenges in the modern era.…”
Section: Impacts Of Nps On Plants Under Hm Toxicitymentioning
confidence: 99%
“…ZnO nanoparticles (NPs) and potassium (K + ) were reported to reduce As toxicity in Vicia faba L. seedlings by increasing NO content in both normal and As-polluted soil. Because zirconium dioxide (ZrO2) NPs have high porosity and adsorption capacity for As(III) and As(V), they may be used for As mitigation because they can bind both As(III) and As(V) and remove As through oxidation of As(III) (Sinha et al, 2023).…”
Section: Genetic Engineering and Nanotechnology In Arsenic Mitigationmentioning
confidence: 99%
“…The modelling program (GMS 10.2), which aids in the prediction of both water flow and As transport, enables the assessment of potential As content in bodies of water as well as deep and shallow aquifers. By preventing polluted water use in drinking and irrigation, such modelling software, in conjunction with advanced numerical modelling, may aid in improved monitoring and health management (Sinha et al, 2023).…”
Section: Genetic Engineering and Nanotechnology In Arsenic Mitigationmentioning
confidence: 99%